A Problem of Perspective: Religions in Africa or African Traditional Religion - Osman Şahin (Şırnak Üniversitesi İlahiyat Fakültesi Dergisi)

(untitled)
This study critiques study of African religions as a singular phenomenon under the umbrella term "African Traditional Religion" and rejects this reductionist approach, suggesting that a more detailed approach that recognises the diversity and plurality of religions on the African continent would allow for more insightful results in the study of religion in Africa. Along with Islam and Christianity, many religions indigenous to African peoples are still practised in Africa. Information about African religions was first provided in the works written mostly by Westerners. The works written by Christian missionaries, anthropologists, soldiers and researchers on religious life in Africa, both before and after the colonial period, have been the trendsetters of the "religion in Africa" literature. In such studies, Africa was analysed as a totality and the term " African Traditional Religion" was created. Besides, these studies were mostly biased, they often looked at religious phenomena from the perspective of Christianity and tried to Christianise them, and even more importantly, they made generalisations and presented all religions as a single religion. Later works by Africans were mostly written by Africans who converted to Christianity. This has led to the continuation of the reductionist and generalising approach in the relevant literature. Studies conducted from this perspective have typically situated African religions within frameworks that emphasize concepts such as the Supreme Being, spirits, ancestor veneration, magic, and sorcery. By highlighting these shared phenomena and oral traditions, this reductionist and orientalist perspective has contributed to the perception of African religions as a singular, cohesive entity. Even today, this effect can be seen in many works. Just as it is an erroneous approach to consider the peoples of Africa as a single race or nation, it is equally problematic to consider the religions of Africa as a single religion. This approach, which places the understanding that there is a single religion in the whole continent based on some similarities observed among the religions in Africa, has prevented the understanding of religious diversity in Africa and African religions. Although it may seem like a practical and problem-free approach, it is obvious that this perspective hinders the understanding of African religions and hence the understanding of Africa. The articles and books analysed in the context of this study have been instrumental in identifying a number of problems associated with this perspective. Many researchers have used the singular term 'Traditional African Religion' and failed to acknowledge the differences between religions. Others have used the term “African Traditional Religion” in the singular, but have stated that religions in Africa should be considered in the plural. Some other researchers have sometimes used a singular and sometimes a plural expression and stated that these can change according to the context, and that both expressions are correct. A small number of researchers also acknowledged that the appropriate term is “religions in Africa” or “African Traditional Religions” in the plural form, in accordance with the points raised in this study. Therefore, this study argues that the individual characteristics of African religions should not be generalised and represented as a single phenomenon, but that a more accurate understanding of these still living religions, with particular emphasis on their differences, will contribute to the understanding of Africa.